2015
DOI: 10.1097/iae.0000000000000611
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Field Spectral Domain Optical Coherence Tomography

Abstract: The novel approach of montaging spectral domain optical coherence tomography images to examine relationships between the choroid, retina, and associated structures adjacent to and outside of the macula may have a number of relevant applications in the study of vitreoretinal interface, paramacular and macular pathologic features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Pichi et al published a similar study as Carrai et al examining eyes with wet age-related macular degeneration, dry age-related macular degeneration, retinitis pigmentosa, adult exudative polymorphous dystrophy and central serous chorioretinopathy. 15 In their study a montage approach was also used to produce a single wide-field SD-OCT image reported as spanning “entire posterior pole spanning ∼200° horizontally and vertically, from equator to equator”, but which did not include the far periphery, as in our images (Figure 3 and Supplemental Figure 12, available at http://aaojournal.org). Finally, Uji and Yoshimura published on ten normal patients using swept source-OCT images that spanned 70° of the retina, in an approach they termed as “extended field imaging.” 16 While these prior studies exclusively used a montaged approach to image the retina periphery, except Uji & Yoshimura, whose images were limited to 70°, our study demonstrates a novel technique to image the far retinal periphery using a 30° steerable lens.…”
Section: Discussionmentioning
confidence: 99%
“…Pichi et al published a similar study as Carrai et al examining eyes with wet age-related macular degeneration, dry age-related macular degeneration, retinitis pigmentosa, adult exudative polymorphous dystrophy and central serous chorioretinopathy. 15 In their study a montage approach was also used to produce a single wide-field SD-OCT image reported as spanning “entire posterior pole spanning ∼200° horizontally and vertically, from equator to equator”, but which did not include the far periphery, as in our images (Figure 3 and Supplemental Figure 12, available at http://aaojournal.org). Finally, Uji and Yoshimura published on ten normal patients using swept source-OCT images that spanned 70° of the retina, in an approach they termed as “extended field imaging.” 16 While these prior studies exclusively used a montaged approach to image the retina periphery, except Uji & Yoshimura, whose images were limited to 70°, our study demonstrates a novel technique to image the far retinal periphery using a 30° steerable lens.…”
Section: Discussionmentioning
confidence: 99%
“…Although this clinical presentation is rarely reported in literature, the administration of steroid in such cases has never been reported. [ 3 4 ] In our case, the increasing in intraretinal cysts was accompanied by visual acuity decay. Therefore, we decided to treat the patient with steroid on an empirical basis.…”
Section: Discussionmentioning
confidence: 50%
“…Correct assessment of the VMI is of particular interest, given that the configuration impacts the treatment response and treatment need in DME, but also in exudative age-related macular degeneration and CME due to uveitis or retinal vein occlusions [17,21,22] . Wide-field OCT studies showed that the vitreous interface can be clearly delineated using this imaging technique [8,10,19] . These findings emphasize the critical role of the correct assessment of the vitreous cortex in respective diseases, which may be facilitated using wide-field SD-OCT.…”
Section: Discussionmentioning
confidence: 99%
“…Wide-field OCT is a new method and of great interest especially when both the periphery as well as the posterior pole need to be assessed in a single scan [11] . So far, widefield and ultra-wide-field OCT were used in order to describe the peripheral retinochoroid morphology and peripheral changes associated with retinitis pigmentosa, choroidal nevi, choroidal melanomas, acute exudative polymorphous vitelliform maculopathy, macular holes, and congenital X-linked retinoschisis [6,8,10,11,19,20] . This is the first study to compare conventional 30° with 55° wide-field SD-OCT using a predefined scanning pattern and grading protocol in order to assess whether widefield SD-OCT may also offer potential benefit in diseases mainly confined to the macular area, and whether it may allow a more precise detection of morphological features outside conventional 30° OCT. We found a strong agreement between both image modalities for morphological features such as IRF, SRF, HE, CWS, and MA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation